Evaluation of anti-diabetic effects of hydroalcoholic extract of green tea and cinnamon on streptozotocin-induced diabetic rats - Ghasem Shokri; Hamed Fathi; Majid Jafari Sabet; Nafiseh Nasri Nasrabadi; Ramin Ataee (Pharmaceutical and Biomedical Research, 2015)
Today diabetes is one of the most common diseases in the world that affects half of the world population. The use of medicinal herbs especially green tea and cinnamon has been taken into consideration for relieving the symptoms of diabetes, but there were some different ideas about their effectiveness. So, this study was conducted to evaluate the effect of cinnamon and green tea extract, individually and in combination, on blood glucose and weight loss in diabetic mice with Streptozotocin (STZ). The experiment was performed on 50 Wistar rats.  A total of 50 rats were divided into 10 groups of 5 and STZ was injected at the dose of 40 mg/kg/day for 5 days intraperitoneally. After diabetes induction, three groups received, 50, 100 and 200 mg doses of green tea extract,  three groups received 50, 100 and 200 mg doses of cinnamon extract  and three final groups received 50, 100 and 200 mg doses of  cinnamon  and green tea in combination by gavages daily for 6 weeks. After each period of treatments, blood glucose and the weight of animals were determined. At the end of the sixth week, blood glucose and weight loss were improved in diabetic rats in a dose-dependent manner and the dose of 200 mg/kg extract cinnamon with green tea had the most appropriate synergic effect.